Targeting galectin-1 overcomes breast cancer-associated immunosuppression and prevents metastatic disease - D'alotto Moreno, Tomas (2013)
Galectin-1 (Gal1), an evolutionarily conserved glycan-binding protein, contributes to the creation of an immunosuppressed microenvironment at sites of tumor growth. In spite of considerable progress in elucidating its role in tumor-immune escape, the mechanisms underlying the inhibitory functions of Gal1 remain obscure. Here, we investigated the contribution of tumor Gal1 to tumor growth, metastasis, and immunosuppression in breast cancer. We found that the frequency of Gal1(+) cells in human breast cancer biopsies correlated positively with tumor grade, while specimens from patients with benign hyperplasia showed negative or limited Gal1 staining. To examine the pathophysiologic relevance of Gal1 in breast cancer, we used the metastatic mouse mammary tumor 4T1, which expresses and secretes substantial amounts of Gal1. Silencing Gal1 expression in this model induced a marked reduction in both tumor growth and the number of lung metastases. This effect was abrogated when mice were inoculated with wild-type 4T1 tumor cells in their contralateral flank, suggesting involvement of a systemic modulation of the immune response. Gal1 attenuation in 4T1 cells also reduced the frequency of CD4(+)CD25(+) Foxp3(+) regulatory T (T(reg)) cells within the tumor, draining lymph nodes, spleen, and lung metastases. Further, it abrogated the immunosuppressive function of T(reg) cells and selectively lowered the expression of the T-cell regulatory molecule LAT (linker for activation of T cells) on these cells, disarming their suppressive activity. Taken together, our results offer a preclinical proof of concept that therapeutic targeting of Gal1 can overcome breast cancer-associated immunosuppression and can prevent metastatic disease.